ABOUT THE TASKS OF OPTIMIZING LOCAL NETWORK OPERATION - Alaminov, Muratbay Xaytbaevich (SCIENCE and SOCIETY, 2026)
The article discusses the issues of optimizing the work of a local area network. Important methods for increasing the efficiency of local area network operations are discussed. It is shown what is important to pay attention to when organizing the work of a local area network effectively.